Beyond clinical trials: the cost saving associated with Dapagliflozin use in Portugal hospital clinical practice - Brito, Dulce (2024)
© 2024 Sociedade Portuguesa de Cardiologia. Published by Elsevier España, S.L.U. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)